1995
DOI: 10.1007/bf00129389
|View full text |Cite
|
Sign up to set email alerts
|

The vegetable rennet of Cynara cardunculus L. contains two proteinases with chymosin and pepsin-like specificities

Abstract: The flowers ofcardoon (genus Qmara)are traditionally used in Portugal for cheese making. In this work the vegetable rennet of the species Cynam oan/uncu/us L. was characterized in terms of enzymic composition and proteolytic specificity of its proteinases (cardosin A and cardosin B). Cardosin A was found to cleave insulin B chain at the bonds Leul5-Tyrl6, Leul7-Vall8 and Phe2.5-Tyr26. In addition to the bonds mentioned cardosin B cleaves also Glul 3-Ala14, Alal4-Leul5 and Phe24-Phc25 indicating that it has a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
113
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 6 publications
(3 reference statements)
9
113
0
4
Order By: Relevance
“…Those proteinases were reported to have a pH optimum of 5.1 and they were classified as aspartic proteinases [27]. Sousa [48] indicated that only two of the three original peaks (peaks 2 and 3) possessed clotting and proteolytic activities; these two proteinases were later named cardosin A (peak 2) and cardosin B (peak 3) [63]. These authors also reported that each cardosin occurs in dimeric form, with apparent molecular masses of 31 and 15 kg .…”
Section: Purification Of Proteinasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Those proteinases were reported to have a pH optimum of 5.1 and they were classified as aspartic proteinases [27]. Sousa [48] indicated that only two of the three original peaks (peaks 2 and 3) possessed clotting and proteolytic activities; these two proteinases were later named cardosin A (peak 2) and cardosin B (peak 3) [63]. These authors also reported that each cardosin occurs in dimeric form, with apparent molecular masses of 31 and 15 kg .…”
Section: Purification Of Proteinasesmentioning
confidence: 99%
“…mol -1 for those in cardosin B. The kinetic parameters associated with hydrolysis of the synthetic peptide Leu-SerPhe-(NO 2 )-Nle-Ala-Leu-oMe were determined, and together with their specificity (see Section 4) they were compared to those of chymosin and pepsin [63]; it was thus shown that cardosin A is similar to chymosin, whereas cardosin B resembles pepsin. These proteinases share pH optima in the acid range, inhibition by pepstatin and preferential cleavage of peptide bonds between hydrophobic residues (as happens with other aspartic proteinases) [64].…”
Section: Purification Of Proteinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…a higher proteolytic activity [19,20]. The localisation of cardosin A has been studied in detail [13].…”
mentioning
confidence: 99%
“…The clotting activity of this extract was first attributed to the presence of three proteolytic enzymes synthesized by the stigmae of those flowers [3], and such (tentatively termed) cynarases 1,2 and 3 were purified and partially characterized [6]. Two new aspartic acid proteinases, (tentatively named) cardosins A and B, were later isolated and are believed to be genetically different from the aforementioned cynarases [17]; in terms of activity and specificity, cardosins A and B are remarkably similar to chymosin and pepsin, respectively [16].…”
Section: Introductionmentioning
confidence: 99%